Influence of sleep on seizures and interictal epileptiform discharges in epilepsy - Jun-Sang Sunwoo (Encephalitis)
Sleep significantly influences seizure occurrence and interictal epileptiform discharges (IEDs) in patients with epilepsy. Sleep-related epilepsy, where seizures occur exclusively or predominantly during sleep, has been observed in various epilepsy syndromes. Understanding the influence of sleep on seizures and IEDs is crucial in the diagnosis, classification, and management of epilepsy. Although there is a bidirectional relationship between sleep and epilepsy, this review focuses on the influence of sleep on seizures and IEDs in epilepsy. Seizures are more common during non-rapid eye movement (NREM) sleep, particularly during stage N2, and are suppressed during rapid eye movement (REM) sleep. Sleep also activates IEDs, increasing the diagnostic yield of EEG recordings. The rate of IEDs increases during NREM sleep, reaches its maximum during stage N3, and decreases during REM sleep. Sleep affects the electrical field of IEDs, with an increase of spiking fields during NREM sleep and a decrease during REM sleep. In the localization of epileptogenic foci, REM sleep is less sensitive but more specific than NREM sleep. Thalamocortical EEG synchronization during NREM sleep and desynchronization during REM sleep underlie their opposing effects on seizures and IEDs. Accumulating evidence has suggested an antiseizure effect of orexinergic antagonism in animal studies. Interventions that promote REM sleep, including orexinergic antagonists, should be studied in the future as novel treatment strategies for epilepsy.